What psychologists should know before applying Grounded theory in their research - Jurgaitytė-Avižinienė, Agnė (Psichologija, 2012)
Lithuanian researchers rarely use Grounded theory (GT) for research in psychology as it poses specific/unique challenges for a researcher and requires additional knowledge. This article covers problematic questions that are important before starting research using GT method.GT is a systematic methodology in the social sciences that attempts to generate theory out of data through a special process of conducting research. GT is a research method that use almost a reverse fashion from traditional positivistic research and at first may appear contradictory to the scientific method used in traditional psychological research. Rather than beginning with literature analyses and developing a hypothesis, the first step is data collection through a variety of methods where data collection and analysis proceeds simultaneously. Article covers how psychology could benefit from using GT as research methodology, especially in fields where studies are just starting and there are no clear findings. GT is especially valuable for the possibility to focus on process research and use and combine a wide variety of data. Article reveals difficulty to talk about GT as a united method because there was a split in usage of GT methodology between authors B. Glaser and A. L. Strauss. Disagreement especially intensified after the K. Charmaz presented her own version of GT. Scientists do not agree about homogeneity of GT and raise questions about different versions and amount of GT versions. It is still unclear how many common elements exist in these versions and what could be named as GT core. The idea about choosing the particular version of GT for research is becoming more prominent than ever. Article follows recommendations of W. A. Babchuk (2009 a) and M. Weed (2009) for choosing one particular GT version, and criticize vague and eclectic use of GT methods. The aim of GT is to generate the “middle range“ theory, and this theory construction purpose raises many questions about validity and adequacy of such idea which is analyzed in article. Various attitudes about theory for different GT versions emerge. Especially clear classical GT (Glaser) position that only this version of method gives adequate conceptual level to generate independent middle rage theory. Literature analyses, hypothesis testing and use of different kind of data are discussed and clarified different position of GT versions in this article. Glaser is famous for his affirmation that only classical GT is real GT and one that can be called a general research methodology. Other versions of GT are regarded by him only as sharing the same vocabulary but using only qualitative inductive method for research. GT uses special vocabulary for procedures that is difficult to translate into Lithuanian without affecting the meaning and requires deep understanding of every word for grasping the meaning of GT process and operating these concepts while doing research. This article is one of the first attempts to translate and use Lithuanian terms of GT in the field of psychological research.
Keywords: grounded theory; applying grounded theory in research; versions; aims; procedures in grounded theory